Aksesibilitas UMKM Terhadap Kredit Usaha Rakyat (KUR) Pada Bank BRI Cabang Payakumbuh - Rossy endah Permata Sari; Irma Suryani Indra; Baitul Hamdi (Jurnal Salingka Nagari, 2025)
This study aims to analyze the  accessibility of Micro, Small, and Medium Enterprises (MSMEs) within the "Kerupuk Sanjai" sector to the People's Business Credit (KUR) initiative administered by PT Bank Rakyat Indonesia (Persero) Tbk, Payakumbuh Branch. Employing a descriptive qualitative methodology, the research delves into the authentic experiences of MSME operators in securing formal financial resources, with particular emphasis on informational transparency, procedural simplicity, and technical impediments. Data collection involved in-depth interviews and on-site observations. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing/verification. The results reveal that although KUR is strategically accessible, its utilization remains obstructed by a notable disparity between regulatory frameworks and practical application. Certain entrepreneurs perceive the credit as readily obtainable and advantageous for capital expansion, whereas others encounter difficulties stemming from intricate administrative demands and insufficient financial education. The study posits that augmenting KUR accessibility necessitates not merely competitive interest rates, but also streamlined bureaucratic processes and more assertive engagement by financial entities. Such enhancements are imperative to foster equitable credit dissemination, thereby bolstering the viability of the informal economy in Payakumbuh.